2009
DOI: 10.1371/journal.ppat.1000366
|View full text |Cite
|
Sign up to set email alerts
|

MAPK ERK Signaling Regulates the TGF-β1-Dependent Mosquito Response to Plasmodium falciparum

Abstract: Malaria is caused by infection with intraerythrocytic protozoa of the genus Plasmodium that are transmitted by Anopheles mosquitoes. Although a variety of anti-parasite effector genes have been identified in anopheline mosquitoes, little is known about the signaling pathways that regulate these responses during parasite development. Here we demonstrate that the MEK-ERK signaling pathway in Anopheles is controlled by ingested human TGF-β1 and finely tunes mosquito innate immunity to parasite infection. Specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
112
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(117 citation statements)
references
References 67 publications
3
112
0
2
Order By: Relevance
“…2E and SI Appendix, Fig. S11) (30). We found that cell number was not affected by U0126 treatment of Aag2 cells (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…2E and SI Appendix, Fig. S11) (30). We found that cell number was not affected by U0126 treatment of Aag2 cells (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 80%
“…Using an orthogonal approach, we took advantage of the ERK pathway inhibitor U0126 that blocks MEK activation across diverse species (29,30), including Drosophila (31,32). Using an antibody that recognizes activated Drosophila Erk, we found that vertebrate insulin induces Erk activation within 15 min (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…P. falciparum histones extracted from merozoites directly stimulate the production of IL-8 and other inflammatory mediators by primary human dermal micro-vascular endothelial cells through a signaling pathway that involves the Src family kinases and p38 MAPK [131]. Malaria parasite development in the mosquito is regulated by a conserved MAPK signaling pathway that mediates the effects of an ingested cytokine [132]. ERK and p38 pathway regulate TNF-α and IL-12 production in macrophage-stimulated with purified P. falciparum GPI [133].…”
Section: The Non-genomic Role Of Vitamin D In Malariamentioning
confidence: 99%
“…The arthropod injects salivary factors into the vertebrate host skin and, at the same time, the vector ingests cytokines [1], growth factors [2], complement components, antibodies and other blood-derived molecules with the blood meal. In both hosts -mammal and arthropod -these molecules can affect the survival and thus infectivity of vectorborne pathogens [3]. Various bioactive molecules in the saliva of blood-feeding arthropods have evolved to facilitate feeding.…”
Section: Introductionmentioning
confidence: 99%